Transient Complete Recovery of Chronic Refractory Idiopathic Thrombocytopenic Purpura after Treatment with Monoclonal Antibody Targeting SARS-CoV-2 Spike Protein - Gogia, Pooja; Xu, Yiqing (Case Reports in Hematology, 2022)
Idiopathic thrombocytopenic purpura (ITP), also known as immune thrombocytopenic purpura, is an immune-mediated acquired disease characterized by transient or persistent decrease of the platelet count due to autoimmune-related destruction of platelets. Therapy for ITP relies on competing and inhibiting the autoantibody binding and destruction (intravenous immunoglobulin and anti-D immunoglobulin and spleen tyrosine kinase (Syk) inhibitor fostamatinib), augmenting platelet production (thrombopoietin receptor agonists), immunosuppression to reduce the autoantibody production, as well as splenectomy. Studies on autoantigens on the platelets suggested epitopes to be located predominantly on the GP IIb/IIIa receptor or integrin αIIbβ3, though the trigger for the development of ITP is unclear. We report a case here of a 37-year-old gentleman who has chronic ITP managed on eltrombopag, who after receiving monoclonal antibody against SARS-CoV-2 (mAb) i.e. casirivimab and imdevimab for his COVID-19 infection, demonstrated complete recovery of his platelet count for a short period of time. We discuss a few potential mechanisms of action and propose further studies to elucidate the therapeutic effect of COVID-19 mAb in ITP.